Proteasome dynamics in response to metabolic changes - Enenkel, Cordula; Ernst, Oliver P. (Frontiers in Cell and Developmental Biology, 2025)
Proteasomes, essential protease complexes in protein homeostasis, adapt to metabolic changes through intracellular movements. As the executive arm of the ubiquitin-proteasome system, they selectively degrade poly-ubiquitinated proteins in an ATP-dependent process. The primary proteasome configuration involved in this degradation is the 26S proteasome, which is composed of a proteolytically active core particle flanked by two regulatory particles. In metabolically active cells, such as proliferating yeast and mammalian cancer cells, 26S proteasomes are predominantly nuclear and actively engaged in protein degradation. However, during nutrient deprivation or stress-induced quiescence, proteasome localization changes. In quiescent yeast, proteasomes initially accumulate at the nuclear envelope. During prolonged quiescence with decreased ATP levels, proteasomes exit the nucleus and are sequestered into cytoplasmic membraneless organelles, so-called proteasome storage granules (PSGs). In mammalian cells, starvation and stress trigger formation of membraneless organelles containing proteasomes and poly-ubiquitinated substrates. The proteasome condensates are motile, reversible, and contribute to stress resistance and improved fitness during aging. Proteasome condensation may involve liquid-liquid phase separation, a mechanism underlying the assembly of membraneless organelles.